Uncertain optimization of composite laminated plates using a nonlinear interval number programming method - Jiang, C.; Han, X.; Liu, G.P. (Computers & structures, 2008)
An uncertain optimization method is suggested to optimize the ply orientations of a composite laminated plate with uncertain material property to obtain a maximum stiffness in the thickness direction. Interval numbers are employed to model the uncertainty of the material property by which only the bounds of the uncertain parameters are needed. An uncertain optimization problem is created based on the elastic waves which are computed by a hybrid numerical method efficiently. A nonlinear interval number programming method is suggested to deal with the uncertain optimization problem. In this method a new order relation of interval number is constructed to transform the uncertain objective function into a deterministic two-objective optimization problem, and a hybrid optimization algorithm is used to eliminate the optimization nesting of the simulation model and whereby improve the computation efficiency. Three numerical examples are investigated, and the optimization results demonstrate the effectiveness of the present method.